Polymyxin B complexation enhances the antimicrobial potential of graphene oxide - Pandit, Santosh; Jacquemin, Lucas; Zhang, Jian; Gao, Zhengfeng; Nishina, Yuta; Meyer, Rikke Louise; Mijakovic, Ivan; Bianco, Alberto; Pang, Chengfang (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The antibacterial activity of graphene oxide (GO) has been widely explored and tested against various pathogenic bacterial strains. Although antimicrobial activity of GO against planktonic bacterial cells was demonstrated, its bacteriostatic and bactericidal effect alone is not sufficient to damage sedentary and well protected bacterial cells inside biofilms. Thus, to be utilized as an effective antibacterial agent, it is necessary to improve the antibacterial activity of GO either by integration with other nanomaterials or by attachment of antimicrobial agents. In this study, antimicrobial peptide polymyxin B (PMB) was adsorbed onto the surface of pristine GO and GO functionalized with triethylene glycol. Methods The antibacterial effects of the resulting materials were examined by evaluating minimum inhibitory concentration, minimum bactericidal concentration, time kill assay, live/dead viability staining and scanning electron microscopy. Results and discussion PMB adsorption significantly enhanced the bacteriostatic and bactericidal activity of GO against both planktonic cells and bacterial cells in biofilms. Furthermore, the coatings of PMB-adsorbed GO applied to catheter tubes strongly mitigated biofilm formation, by preventing bacterial adhesion and killing the bacterial cells that managed to attach. The presented results suggest that antibacterial peptide absorption can significantly enhance the antibacterial activity of GO and the resulting material can be effectively used not only against planktonic bacteria but also against infectious biofilms.